KEEFEKTIFAN MODEL PEMBELAJARAN EXPLICIT INSTRUCTION TERHADAP HASIL BELAJAR MATEMATIKA MATERI PERBANDINGAN DAN SKALA KELAS V - Nahara Amari, Syarifa; ., Sumarno; Eka, Ervina (Jurnal Imiah Pendidikan dan Pembelajaran, 2018)
The Effectiveness of Explicit Instruction Learning Model on Learning Outcomes Mathematical Subjects of Comparative Material and Class V Scale of MI Maarif Krakal Alian Kebumen. The purpose of this study was to determine the effectiveness of the use of Explicit Instruction learning models on Mathematics learning outcomes Fractions and class V scales MI Maarif Krakal. This research method is quantitative research in the form of Pre Experimental Design with the design of One-Group Pretest-Posttest Design. The population of this study was all fifth grade students of MI Maarif Krakal. The samples taken were all students of class V which numbered 25 students using the Nonprobability Sampling technique in the form of saturated sampling. The data in this study were obtained through interviews, documentation, and tests. The results of the analysis of research data after getting treatment using the Explicit Instruction learning model obtained 21 students who completed and 4 students who have not been completed. Calculation of the value of learning outcomes at the average value of posttest > pretest is 65.60 > 47.44. This is evident in the final analysis using the t test known that the result of tcount > ttable is 8.316 > 1.711 at a significant tariff of 5%. The average value of attitudes and skills of students also increases by using the Explicit Instruction learning model. From the analysis it can be concluded that the Explicit Instruction learning model is effective against the mathematics learning outcomes of the fraction material and class V scale MI Maarif Krakal. Keywords: Explicit Instruction Model, learning outcomes